2007
DOI: 10.1007/s00411-007-0124-1
|View full text |Cite
|
Sign up to set email alerts
|

Inter-comparison of absorbed dose rates for non-human biota

Abstract: A number of approaches have been proposed to estimate the exposure of non-human biota to ionizing radiation. This paper reports an inter-comparison of the unweighted absorbed dose rates for the whole organism (compared as dose conversion coefficients, or DCCs) for both internal and external exposure, estimated by 11 of these approaches for selected organisms from the Reference Animals and Plants geometries as proposed by the International Commission on Radiological Protection. Inter-comparison results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(41 citation statements)
references
References 13 publications
3
38
0
Order By: Relevance
“…In part, this is a consequence of the different organisms considered in the three models. It is also in agreement with other comparisons of models/approaches used to estimate exposure of biota which have demonstrated that the dosimetry components generally estimate comparable results [1][2][3]. The greater variability observed in estimated RQ values between models when assuming 1 Bq kg −1 in freshwater sediments may be the consequence of RESRAD-BIOTA using terrestrial soil-soil water k d values rather than freshwater sediment-water k d values [10].…”
Section: Variation In Estimated Rq Valuessupporting
confidence: 86%
See 1 more Smart Citation
“…In part, this is a consequence of the different organisms considered in the three models. It is also in agreement with other comparisons of models/approaches used to estimate exposure of biota which have demonstrated that the dosimetry components generally estimate comparable results [1][2][3]. The greater variability observed in estimated RQ values between models when assuming 1 Bq kg −1 in freshwater sediments may be the consequence of RESRAD-BIOTA using terrestrial soil-soil water k d values rather than freshwater sediment-water k d values [10].…”
Section: Variation In Estimated Rq Valuessupporting
confidence: 86%
“…A number of models/approaches/tools to estimate the exposure of wildlife to ionising radiation have been produced or are being developed for use in assessments [1][2][3]. Many of the approaches use some form of tiered (iterative) assessment consistent with approaches used for other stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates were made for seven radionuclides ( 3 H, 14 C, 60 Co, 90 Sr, 137 Cs, 238 U and 241 Am) chosen to cover a range of energies and radiation types. The results of this exercise are described fully by Vives i Batlle et al [5].…”
Section: Intercomparison Exercisesmentioning
confidence: 61%
“…1) The ICRP has assessed absorbed fractions (AFs), the fraction of energy emitted by a radiation source which is absorbed within the target organ, in Reference Animals and Plants for understanding dose responses, radiation-related side-effects and the consequences of such effects. 2) The assessment has been performed only in the whole bodies of the Reference Animals for simplified dosimetric models which do not include internal organs except for the Reference Deer. 3) Besides the efforts of ICRP for radiation protection of animals, many various studies have been done on dosimetry of small animals, such as rats and mice, which are widely used in preclinical evaluations of radiopharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%